Research progress on the predictive value of electrocardiographic indicators in the diagnosis and prognosis of children with vasovagal syncope - Zhao, Ting; Wang, Shuo; Wang, Miao; Cai, Hong; Wang, Yuwen; Xu, Yi; Zou, Runmei; Wang, Cheng (Frontiers in Cardiovascular Medicine, 2022)
Neurally mediated syncope (NMS) is a common type of syncope in children in clinical practice, among which vasovagal syncope (VVS) is the most frequent. In recent years, more and more researches have been carried out to assess the diagnosis and prognosis of VVS. The electrocardiographic indicators such as heart rate variability (HRV), QT dispersion (QTd), P wave dispersion (Pd), ventricular late potentials (VLP), deceleration ability of heart rate (DC) etc. are easy to obtain and inexpensive. With the help of electrocardiographic indicators, the diagnostic procedure and individualized treatment strategies of pediatric VVS can be optimized. This article reviews the value of electrocardiographic indicators in the diagnosis and prognosis of children with VVS.